Efektivitas Pelayanan Prima Pada Program Layanan Lumpur Tinja Terjadwal (L2T2) di Kantor Cabang Pemasaran Air Limbah PDAM Tirtanadi Kota Medan - Lubis, Arafani Khairunisa; Mahardika, Ananda (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
The Scheduled Fecal Sludge Service Program (SFSSP) is a service program for suctioning fecal sludge from septic tanks belonging to people's homes which is carried out periodically and on a schedule. This research aims to determine the effectiveness of excellent service in the Scheduled Desludging Service Program (SFSSP) at the Waste Water Marketing Branch Office of PDAM Tirtanadi, Medan City. The type of research used in this research is descriptive research with qualitative data analysis, namely problem solving procedures which are researched by means of observation, interviews by describing the condition of the research object based on directly visible facts and the public's responses as they are. Based on the research results, it is known that the services provided by PDAM Tirtanadi to the community with the Scheduled Fecal Sludge Service Program (SFSSP) have been running since the start of the program in 2020, but the services provided by the program cannot yet be said to be excellent. This is because the service does not fully meet the indicators of excellent service. PDAM Tirtanadi has not been able to provide comprehensive outreach or understanding so that many people do not knowING about the existence of this program. However, PDAM Tirtanadi is able to provide a fairly systematic schedule, so that desludging can take place more easily and in accordance with Standard Operating Procedures (SOP).